Stabilization of sulphidic mine tailings for prevention of metal release and acid drainage using cementitious materials: a review. Issue 4 (2nd July 2007) - Nehdi, Moncef; ,
Abstract : Environmental contamination produced by acid generating mines currently represents the largest environmental liability of the mining industry and necessitates the development of novel techniques for its mitigation. This paper reviews existing literature on stabilization of sulphidic mine tailings and prevention of acid mine drainage (AMD). It is shown that stabilization using ordinary portland cement in combination with pozzolanic and cementitious materials could be a viable option. However, variation of mine waste constituents and their interactions with different binders thwart the formulation of a generalized recipe for stabilization and further necessitate research to explore the optimal waste-binder proportions of the stabilized system components for the particular mine tailings under consideration. The demonstrated effective utilization of industrial by-products (fly ash, slag, cement kiln dust, etc.) in the preparation of modified cementitious materials for stabilization of sulphidic mining waste reinforces further interest in this area, not only to cope with acid mine drainage, but also to utilize abundant discarded industrial by-products for various beneficial considerations. This paper critically examines various mine tailings stabilization techniques in the literature, identifies the fundamental mechanisms controlling their performance and the intrinsic parameters of stabilization systems, along with the tailings-binder interaction mechanisms and performance assessment tools for stabilized tailings.